Virtual educational video tour of the central surgical installation reduce anxiety of preoperative patients - Purnamasari, Vita; Aisyah Nur Azizah; Nia Handayani (Universitas 'Aisyiyah Yogyakarta, 2024)
Surgery is one of the medical procedures that will give an emotional reaction to the patient. Stressors that appear can be in the form of physiological stress, psychological stress (anxiety and fear) and social stress. The anxiety felt in pre-operative patients is mostly caused by excessive worry about what the patient will face during the surgical procedure. The implementation of pre-operative orientation can provide patients with an understanding of their condition and avoid negative things that arise in patients due to ignorance about the treatment they will receive. Orientation about the Central Surgical Installation room can be one of the interventions to increase patient knowledge so that anxiety can decrease. This research aims to develop educational media in reducing anxiety through audiovisual videos of the orientation of the Central Surgical Installation (IBS) room. The type of research planned is a quasy experiment research with a Pretest-Posttest Control Group Design approach. Sampling using accidental sampling. Data analysis used the Wilcoxon Signed Rank Test and Mann-Whitney Test. The results showed that there was a significant difference in anxiety between the intervention group and the control group after being given an educational intervention with a virtual video tour with a P value of <a (0.05) which means that there was a significant influence between the provision of virtual tour education in the IBS room on the anxiety of preoperative patients. This study has a significant influence on providing education using virtual tour videos to reduce anxiety in preoperative patients.